Comparison of Mental Disorders between Home Owner Residents and Nurse Homes Elders - Saeid Rezayi; Mahshid Manouchehri (University of Social Welfare & Rehabilitation Sciences, 2008)
Objectives: Ageing phenomenon is a naturals process. Actually, ageing includes biological changes that occurs in bioorganic and psychosocial situations in duration of life long. These changes make decreases in physical, mental powers and accomplishment in unawareness variety. These changes cause decreased physical energy and adaptation of a person. In other hands it causes decreased individual's adaptation in sudden changes and changes in structure and function in different organs among people. Ageing refer to persons who aged over 60 years. The Purpose of this study was to investigate psychosocial outcomes of older people who segregated from their homes. Methods & Materials: This study was a comparison study between home owners and nursing home residents. The participants were 100 older people (50 home owner and 50 owner kahrizak nursing home in Tehran). SCL90 scale was applied for comparison of mental disorders in the two elder groups. The hypothesis was comparison of mental disorders between home owners and nursing home residents. Results: The result showed a significant different (P<0.01, and P<0.05) between home owner and nursing home residents (in both men and women) in mental health variables. Conclusion: Older adults living in nursing homes had more problems in their mental situation than home owner resident elders.